Incidence of multiple herbicide resistance in annual bluegrass (Poa annua) across southeastern Australia. Issue 4 (4th July 2020) - Barua, Rajesh; Boutsalis, Peter; Malone, Jenna; Gill, Gurjeet; Preston, Christopher
Abstract: Annual bluegrass ( Poa annua L.) is a problematic annual weed in established turf where the intensive use of herbicides has resulted in the evolution of herbicide resistance. In 2017, 31 populations of P. annua suspected to be resistant to herbicides commonly used to control this weed in turf were collected from golf courses across southeastern Australia to check the resistance status to different herbicide groups. All populations were found to be resistant to multiple turf herbicides. Dose–response experiments confirmed resistance to propyzamide, simazine, rimsulfuron, foramsulfuron, endothall, and pinoxaden. Levels of resistance to rimsulfuron (>56-fold), foramsulfuron (>19-fold), endothall (>7-fold), and pinoxaden (>4.3-fold) compared with the susceptible population were high, but levels of resistance to propyzamide (>2-fold) and simazine (>2-fold) were lower. Considerable variation in resistance to endothall and pinoxaden was observed among the populations of P. annua . Target-site resistance was confirmed for acetolactate synthase and acetyl-CoA carboxylase inhibitors, but not for photosystem II and microtubule assembly inhibitors. This study documented the extensive resistance to herbicides in P. annua from turf in Australia. Three of the populations investigated exhibited multiple resistance to herbicides from five mechanisms of action. The identification of multiple-resistant P. annua on several golf courses is a serious concern for turf managers.